2021
DOI: 10.1192/j.eurpsy.2021.383
|View full text |Cite
|
Sign up to set email alerts
|

Do personality traits influence the stigmatizing attitudes toward people with mental illness? A web-survey among university students

Abstract: IntroductionPeople from the general population often tend to believe that psychiatric patients may be incurable, dangerous, and unpredictable. Stigma represents a critical issue which should be defeated. In spite of the interest of research, little is known about the relationship between personality traits and level of stigma toward people with mental illness.ObjectivesTo evaluate whether certain personality traits can influence the level of stigma towards mental illness in a population of university students.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous research revealed that certain personality traits (e.g., low agreeableness and openness to experience) were more closely related to stigmatizing attitudes (Fusar-Poli et al, 2021;McCrae et al, 2007). It is considered that certain personality traits, such as need for cognitive closure (NFC), may become more prominent for stigmatizing attitudes in the unknown context of the pandemic.…”
mentioning
confidence: 99%
“…Previous research revealed that certain personality traits (e.g., low agreeableness and openness to experience) were more closely related to stigmatizing attitudes (Fusar-Poli et al, 2021;McCrae et al, 2007). It is considered that certain personality traits, such as need for cognitive closure (NFC), may become more prominent for stigmatizing attitudes in the unknown context of the pandemic.…”
mentioning
confidence: 99%